What lies beneath? The material agency and politics of the underground in urban regeneration. Issue 126 (November 2021) - Ruming, Kristian; McGuirk, Pauline; Mee, Kathleen
Abstract: Drawing on a growing literature on vertical and volumetric urbanism and a recent "subterranean turn" in geography, this paper explores the materiality and material agency of the underground and its entwinement with aboveground planning and development. The paper focuses on urban regeneration and planning in Newcastle, Australia: a city where underground coal mining has been deeply entwined in the establishment, economic prosperity, and geographical spread of the city, leaving the city undermined by multiple mine shafts (voids). Our analysis reveals the interconnectedness of vertical and horizontal capacities of the city and how this has shaped recent urban regeneration initiatives. Positioning the underground as a vital and agentic element of the wider urban assemblage and constitutive of the aboveground, we explore how its material presence (or, in this case, absence) is made visible through mapping techniques, and how its agency shapes the form, function and politics of urban development. Our analysis empirically traces the material agency of the underground at two scales. First, we examine how underground voids affect construction and financial viability at the building level. Second, we unpack how the presence of underground voids across the inner-city shapes precinct and city-scale regeneration initiatives, influencing the form and function of the city. The paper builds our understandings of volumetric urbanism and the subterranean, teasing out empirically the intertwinement of the aboveground and underground, and surfacing the material agency of the underground and its influence on the pathways and politics of aboveground urban development.